Evaluation of a partial retinal surface tear by optical coherence tomography - Kawazoe K (Dove Medical Press, 2011)
Kenji Kawazoe1, Hisato Ohno1, Kenji Inoue1, Yasuo Yanagi21Inouye Eye Hospital, 4-3 Kanda-Surugadai, Chiyoda-ku, Tokyo, Japan; 2Department of Ophthalmology, University of Tokyo School of Medicine, 7-3-1 Hongo Bunkyo-ku, Tokyo, JapanAbstract: Differential diagnosis of retinal hemorrhage and partial tear of the retinal surface may be difficult in some cases. A 62-year-old woman was mistakenly followed-up for small retinal hemorrhages for more than 1 year. Blocked fluorescence specific to retinal hemorrhage was not observed by fluorescein angiography (FAG). Optical coherence tomography (OCT) clearly showed defects of the retinal surface indicating partial tears of the surface at the vitreoretinal juncture and not hemorrhage. OCT is a useful and noninvasive device for the differential diagnosis of retinal hemorrhage and partial tear of the retinal surface.Keywords: OCT, differential diagnosis, retinal surface defect,vitreoretinal juncture over retinal vessels